Analysis Of The Effect Of Gamelan Metaverse On Acceptance Of Music Education Methods Using Technology Acceptance Model 2 - Daniel Renato Marlen; Putri Nastiti; Clara Hetty Primasari; Yohanes Priadi Wibisono; Julius Galih Prima Negara (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Gamelan Metaverse traditional gamelan musical instruments originating from Yogyakarta in virtual reality. The development of this VR is still relatively new, so limitations need to be identified. This research using the technology acceptance model 2 (TAM 2) method to identify factor-factor that influence acceptance of the gamelan metaverse in music classroom learning. The issue unknown factors hindering the Gamelan Metaverse towards music education as a music learning medium. The method used a deductive research method with quantitative research methods. This study focused on numbers such as quantitative data compiled using statistical analysis methods with SPSS 26 and AMOS software. The factors or variables used included perceived usefulness, intention to use, usage behavior, perceived ease of use, and mobility. The sample data recorded were 35 respondents, including active students from UAJY and ISI. The conclusion revealed that the Gamelan Metaverse has not been effective as an alternative to music education learning because it has not met the criteria in the hypothesis.